Universal elevator round trip time calculation for general traffic conditions with extension to batch arrivals. (September 2022) - So, Albert; Al-Sharif, Lutfi; Chan, Ricky
Recent studies have revealed that the dominant traffic pattern of a modern high-rise building is much more complicated than the conventional up-peak model, i.e. incoming traffic only, upon which the popular formula of round trip time (RTT) calculation is based. RTT calculation is still recommended by ISO 8100:32:2020 and CIBSE Guide D: 2020 to precede any computer simulation. Nowadays, the concern is more on the lunch peak with a mixture of incoming, outgoing and interfloor traffic patterns. Moreover, the independent one-passenger arrival model should be replaced by the more practical batch arrival model, in particular during lunch-time peak. This article first summarizes what were previously published on the universal RTT evaluation for mixed traffic conditions, highlights the main arguments, updates and supplements some previously introduced formulae such as that related to coincidental stops, uses more symmetrical and easily manipulated graphics, and, second in particular, brings in the concept of batch arrivals of any desirable probability distribution, where the conventional independent one-passenger arrival up-peak model now becomes a special case. A step-by-step presentation is adopted for convenient application of this universal calculation approach by designers and the detailed verification of the whole process by Monte Carlo simulation is also included. Practical applications: Round trip time calculation is still recommended the first step of traffic design by the industry but it should reasonably include the consideration of mixed traffic patterns, versus a pure incoming (i.e. up-peak) approach in the past. Such universal RTT calculation was described in several articles previously, but with some missing details. Here, the whole process is summarized, updated and presented in a more graphical way for convenient use by designers. Furthermore, the more contemporarily practical batch passenger arrival mode is included in this universal RTT model as an extension to the methodology so that what are discussed in this article include incoming, outgoing, interfloor traffic patterns with batch arrival consideration. It is hoped that this article could provide a comprehensive universal RTT methodology that can eventually be popularly applied globally by designers and consultants.